On the lattice of cyclic codes over finite chain rings - Fotue-Tabue, A.; Mouaha, C. (Algebra and Discrete Mathematics, 2019)
In this paper, R is a finite chain ring of invariants (q, s), and ℓ is a positive integer fulfilling gcd(ℓ, q) = 1. In the language of q-cyclotomic cosets modulo ℓ, the cyclic codes over R of length ℓ are uniquely decomposed into a direct sum of trace-representable cyclic codes over R and the lattice of cyclic codes over R of length ℓ is investigated.